2014
DOI: 10.1177/0886260514535261
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Domestic Violence and Acceptance of Intimate Partner Violence Among Out-of-School Adolescent Girls in Iwaya Community, Lagos State

Abstract: Gender-based domestic violence (DV) comes at great costs to the victims and society at large. Yet, many women hold the view that intimate partner violence (IPV) against women is appropriate behavior. This study aimed at exploring the nexus of experience of different forms of DV and acceptance of IPV as appropriate behavior. Using data from a survey of 480 out-of-school adolescent girls, the researcher shows that psychological abuse is a significant predictor of approval of DV resulting from the wife's failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
(18 reference statements)
1
22
1
Order By: Relevance
“…27 , 28 , 31 The preponderance of emotional abuse may reflect the perception of partners that emotional abuse is least offensive and more tolerable by their spouse or the community in which they live. 32 Additionally, most cultures in Nigeria place the male as the ‘father’ of the household, 33 as such, wives are not spared of insults when being reprimanded. Paradoxically, some women express approval of emotional abuse from partners when home chores are not completed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 , 28 , 31 The preponderance of emotional abuse may reflect the perception of partners that emotional abuse is least offensive and more tolerable by their spouse or the community in which they live. 32 Additionally, most cultures in Nigeria place the male as the ‘father’ of the household, 33 as such, wives are not spared of insults when being reprimanded. Paradoxically, some women express approval of emotional abuse from partners when home chores are not completed.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, some women express approval of emotional abuse from partners when home chores are not completed. 33 In African settings, emotional abuse, harassment and sexual abuse are sometimes trivialised. 8 , 33 As such, past research and advocacy have focused majorly on physical abuse, neglecting other forms of abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of domestic violence victims were female, while perpetrators were usually male. Men who committed violence against women were often less educated (Envuladu et al, 2012;Kunnuji, 2014). Another study concluded that having more children can increase the risk of child abuse by the parent (Chan, 1994;Gibson, 2012;Yoo and Huang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, on one hand, it was recently noted that exposure to and experience of sexual partner violence was associated with tolerance of sexual partner violence by both boys and girls (Mason-Jones et al, 2016;Pöllänen et al, 2018). Adolescents who were psychologically abused, on the other hand, were more likely to endorse domestic violence (Kunnuji, 2015). Finally, exposure to violence has poor psychosocial outcomes for adolescents and contributes to intergenerational transmission of violence.…”
Section: Correlates and Effects Of Exposure To Violence And Beliefs Amentioning
confidence: 99%